Should the distal tears of aortic dissection be treated? The risk of distal tears after proximal repair of aortic dissection. (15th June 2018) - Zhang, Simeng; Chen, Yanqing; Zhang, Yongxue; Shi, Dongchen; Shen, Yu; Bao, Junmin; Zhao, Zhiqing; Feng, Xiang; Feng, Rui; Zhou, Jian; Lu, Qingsheng; Jing, Zaiping
Abstract: Background: Patients with distal residual after proximal repair of aortic dissection (AD) have shown unsatisfactory long-term prognosis. However, possible mechanisms and risk factors for distal aortic segmental enlargement (DSAE) have been poorly understood. Methods: We analyzed 962 AD patients repaired to the descending aorta between 1999 and 2014. Aortic morphological characteristics of 419 patients (including 75 DSAE and 344 non-DSAE patients) were investigated and compared. Potential risk factors associated with DSAE were explored using logistic regression analysis or natural logarithmic transformation. Logistic multi regress equations were performed to identify independent risk factors. Results: Independent risk factors of DSAE are listed as follow: more tears in the thoracic descending aorta (odds ratio [OR], 1.65; 95% confidence interval [CI], 1.24 to 2.19; P = .0005); fewer tears in the infra-renal abdominal aorta (OR, 3.00; 95% CI, 2.04 to 4.55; P < .0001); closer distance of the first intimal tear to the left subclavian artery (OR, 1.51; 95% CI, 1.28 to 1.69; P < .0001); larger average distance between tears (OR, 11.81; 95% CI, 3.39 to 41.08; P = .0001); larger maximum distance between two tears (OR, 1.79; 95% CI, 1.48 to 2.16; P < .0001), and larger area of remained tears (OR, 1.56; 95% CI, 1.38 to 1.76; P < .0001). Conclusions: The location and size of remained tears are the key risk factors of DSAE patients. Long-segment aortic repair and aggressive exclusion of all distal tears located on the thoracic descending aorta in their initial therapy will be an optimal strategy. Highlights: The location and size of the remaining tears are identified as risk factors of distal segmental aortic enlargement. Long-segment aortic repair in their initial therapy shows potential to have a better prognosis. All distal tears located on the thoracic descending aorta should be repaired, from proximal to distal.